The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.sbspro.2015.01.411
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management Accounting Practices in Small Medium Manufacturing Firms

Abstract: This study investigates factors and barriers which influence the practice of environmental management accounting (hereafter known as EMA). The institutional theory is employed and data is collected via questionnaire. This study focuses on small medium enterprises (hereafter known as SMEs) specifically, Malaysian small medium manufacturing firms. The results indicate that most firms have a budget allocation for environmental activities and practice physical EMA. The study argues that coercion is a dominant fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
87
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 14 publications
13
87
4
2
Order By: Relevance
“…This means that H3, which hypothesised a significant and positive relationship between perceived mimetic pressures and social sustainability, was supported as well leading to the rejection of the null hypothesis. The results of this study contradict previous empirical evidence from studies [67,68] which suggested that mimetic isomorphism had no impact especially on environmental sustainability practices. However, the results are consistent with findings of a study which established a statistically significant relationship between mimetic isomorphism and sustainable development practices [8].…”
Section: Discussioncontrasting
confidence: 93%
“…This means that H3, which hypothesised a significant and positive relationship between perceived mimetic pressures and social sustainability, was supported as well leading to the rejection of the null hypothesis. The results of this study contradict previous empirical evidence from studies [67,68] which suggested that mimetic isomorphism had no impact especially on environmental sustainability practices. However, the results are consistent with findings of a study which established a statistically significant relationship between mimetic isomorphism and sustainable development practices [8].…”
Section: Discussioncontrasting
confidence: 93%
“…They applied the EMA assessment template provided by IFAC (2005). Despite the significance of EMA, the adoption and implementation of EMA are still relatively weak in a developing country like Malaysia (Jamil et al, 2015). Jalaludin et al (2010) provided that EMA implementation is moderate, but their results produce positive correlations between EMA (monetary and physical) and environmental performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The literature has demonstrated the many benefits reaped from EMA such as superior cost-saving and sustaining competitive advantage (Jasch, 2003;Faudah & Arisman, 2013;Jaidi, Noordin, Mail, & Lim, 2018). Despite the importance and benefits of EMA, the adoption and implementation of EMA in many developing countries such as Malaysia is still weak (Jamil, Mohamed, Muhammad and Ali, 2015). Although EMA is important to improve a company's environmental performance, research of EMA in Malaysia is still relatively new and scant (Mokhtar, Jusoh, & Zulkifli, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Defensive strategy and hierarchical culture are factors that impede the application of environmental management accounting. Jamil et al (2015) conducted a survey of the factors and barriers that affect the practice of environmental accounting management in small and medium firms in Malaysia. The results indicate that most firms allocate funds for environmental activities and environmental accounting practices in non-monetary aspects.…”
Section: Literature Reviewmentioning
confidence: 99%